Potential Utility of Visually AcceSAble Rembrandt Images Assessment in Brain Astrocytoma Grading. Issue 2 (March 2016) - Yu, Jing; Wang, Min; Song, Jiacheng; Huang, DongYa; Hong, Xunning
Abstract : Objective: The aim of this study was to evaluate the predictive value of multivariate factors of Visually AcceSAble Rembrandt Images (VASARI) in brain astrocytoma grading. Methods: Presurgical magnetic resonance images of 126 patients with brain astrocytomas (World Health Organization grade 2, n = 38; grade 3, n = 36; grade 4, n = 52) were rated by 2 neuroradiologists for tumor size, location, and tumor morphology by using a standardized imaging feature set VASARI. Results: Significant differences were noted in 12 factors of VASARI including enhancement quality, enhancing proportion, noncontrast enhancing tumor proportion, necrosis proportion, edema proportion, hemorrhage, thickness of enhancing margin, definition of the enhancing margin, pial and ependymal invasion, enhanced tumor crossing midline, and satellites between brain astrocytoma grades (grades 1-IV, P < 0.05). On multivariate regression analysis, enhancement quality was an independent diagnostic factor for high-grade brain astrocytoma, whereas edema proportion was an independent diagnostic factor in differentiating grade 2 and grade 3. Noncontrast enhancing tumor proportion was a predictive factor in the diagnosis of grade 4 astrocytoma. Receiver operating characteristic analysis illustrates edema proportion score higher than 2 with sensitivity of 86.1% in differentiating grade 2 and grade 3 astrocytoma. Noncontrast enhancing tumor proportion scores 4 or lower has high sensitivity (92.3%) but moderate specificity (50.0%) in differentiating grade 3 and grade 4 astrocytoma. Conclusions: Our data illustrate that magnetic resonance features of VASARI especially enhancement quality, edema proportion, and noncontrast enhancing tumor proportion provided precise and detailed information of astrocytoma grading and suggested that prediction of astrocytoma grading is based on VASARI as an adjunct to biopsy. Abstract : Supplemental digital content is available in the text.